KEKUATAN KAPITAL SIMBOLIK OSCAR WILDE THE TROUBLED GENIUS - agry pramita (Jurnal Lingua Idea, 2016)
This research explains a sociological reading about Oscar Wilde. This action aims to develop an analysis of the author’s life with some considerations which support his work in literary world. In addition this research also aims to construct a valid sociological reading. The sociological reading will be done by using the concept of sociological approach by Pierre Bourdieu. According to his statement, the concept of cultural arena brings the new light in sociology where the sociological phenonenon is no longer the only main consideration. In expanding the approach, Bourdieu adds agen and structure as the new tools. In this writing, almost all Oscar Wilde’s literary works use social critic as the main theme. Historically speaking, this thing is closely related to the era of Victoria age. This history enrich Wilde’s works in the field of literary world.